Supercritical carbon dioxide as a tool for improving the biocompatible properties of biopolymer and tissue specific scaffolds for tissue engineering - E. A. Nemets; A. E. Lazhko; A. M. Grigoryev; V. Yu. Belov; V. A. Surguchenko; Yu. B. Basok; A. D. Kirillova; V. I. Sevastianov (Вестник трансплантологии и искусственных органов)
Objective: to investigate the efficacy of supercritical carbon dioxide (sc-CO2) for enhancштп the biocompatibility of biopolymer scaffolds from biodegradable materials and tissue-specific scaffolds from decellularized porcine liver slices (PLSs) or fine porcine cartilage particles (FPCPs).Materials and methods. Biopolymer scaffolds of a polyoxy(butyrate-co-valerate) and gelatin copolymer composition, 4 mm in diameter and 80 mm in length, were formed by electrospinning (NANON-01A, MECC CO, Japan) and stabilized by incubation in glutaraldehyde vapor for 48 hours at room temperature. For decellularization, PLSs and FPCPs were incubated under periodic stirring in buffer (pH = 7.4) solutions of sodium dodecyl sulfate (0.1%) and Triton X-100 with increasing concentrations (1, 2, and 3%). Treatment in a sc-CO2 atmosphere was done at 150–300 bar pressure, 35 °C temperature, and 0.25–2.5 mL/min flow rate of sc-CO2 for 8–24 hours. 10% ethanol was introduced as a polarity modifier. Cytotoxicity was studied according to GOST ISO 10993-5-2011. The growth of NIH/3T3 in the presence of samples was studied using an interactive optical system IncuCyte Zoom.Results. The effect of the sc-CO2 flow rate and pressure, and the effect of addition of ethanol, on the biocompatibility of scaffolds was investigated. It was found that treatment at a low sc-CO2 flow rate (0.25 mL/min) does not achieve the required cytotoxicity. Complete absence of cytotoxicity in biopolymer scaffolds was achieved in the presence of 10% ethanol, at a sc-CO2 flow rate of 2.5 mL/min, 300 bar pressure and 35 °C temperature after 8 hours of treatment. Effective removal of cytotoxic detergents from decellularized liver occurs already at a 150-bar pressure and does not require the addition of ethanol. Adding ethanol to sc-CO2 eliminates not only the cytotoxic, but also the cytostatic effect of tissue-specific scaffolds.Conclusion. Sc-CO2 treatment is an effective way to enhance the biocompatibility of three-dimensional porous matrices produced using cytotoxic substances: bifunctional crosslinking agents for biopolymer scaffolds and surfactants in the case of tissue-specific matrices. Addition of ethanol as a polarity modifier improves the treatment efficiency by eliminating both cytotoxic and cytostatic effects.